Magnetoresistance Anomaly in Topological Kondo Insulator SmB6 Nanowires with Strong Surface Magnetism. Issue 7 (21st May 2018) - He, Xingshuai; Gan, Haibo; Du, Zongzheng; Ye, Bicong; Zhou, Liang; Tian, Yuan; Deng, Shaozhi; Guo, Guoping; Lu, Haizhou; Liu, Fei; He, Hongtao
Abstract: Topological Kondo insulators (TKIs) are a new class of topological materials in which topological surface states dominate the transport properties at low temperatures. They are also an ideal platform for studying the interplay between strong electron correlations and topological order. Here, hysteretic magnetoresistance (MR) is observed in TKI SmB6 thin nanowires at temperatures up to 8 K, revealing the strong magnetism at the surface of SmB6 . It is also found that such MR anomaly exhibits an intriguing finite size effect and only appears in nanowires with diameter smaller than 58 nm. These nontrivial phenomena are discussed in terms of the latest Kondo breakdown model, which incorporates the RKKY magnetic interaction mediated by surface states with the strong electron correlation in SmB6 . It would provide new insight into the nature of TKI surface states. Additionally, a non‐monotonically temperature dependent positive magnetoresistance is observed at intermediate temperatures, suggesting the possible impurity‐band conduction in SmB6, other than the surface state transport at low temperatures and the bulk‐band transport at high temperatures. Abstract : SmB6 nanowires exhibit abnormal hysteretic magnetoresistance below 8 K, indicating the emergence of strong surface magnetism. This magnetoresistance anomaly also shows a nontrivial dependence on the size of the nanowires. These phenomena can be understood in terms of the latest Kondo breakdown model, which incorporates the RKKY magnetic interaction mediated by surface states with the strong electron correlation in SmB6.